Participatory forage production for biomass and seed production through different sowing methods in Afar Regional State, Ethiopia: In the Case of Afambo District of Afar Ethiopia - Anwar Seid Hassen (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2019)
This experiment was conducted with the objective of to evaluate effect of sowing methods on biomass, seed and planting materials production with participatory of the local community in Afambo districts. Accordingly, the biomass yield of Panicum antidotale, Cenchrus ciliaris, Lablab purpureus (147), Vigna unguiculata (9333), and sowing by drill method was significantly higher than sowing by broadcasting methods. Drilling method was having significant effect (P ≤ 0.05) on days of seed maturity, seed yield and plant height than broadcast method. But there was no significant effect (P ≤ 0.05) of sowing methods on days of emergence and diseases incidence on both grasses and legumes. Similarly, drilling method was having significant effect (P ≤ 0.05) on herbage yield than broadcast method on both grasses and legumes. But there was no significant effect (P ≤ 0.05) of sowing methods on days of flowering, days of seed setting and on both grasses and legumes. According to the trial agro pastoralist perception P. antidotale was selected first followed by Cenchrus ciliaris for their palatability, bio mass yield, drought tolerance, due to its vegetation and morphological performance.